State Financial Education on Instagram by Surakarta’s State Treasury Office: a Content Analysis - Satria, Ardy; Dwi Astuti Nurhaeni, Ismi; Rahmanto, Andre (Universitas Muhammadiyah Yogyakarta, 2025)
Economic uncertainty in the era of globalization requires the public to enhance their literacy regarding state finances. However, access to information about state finances remains limited, making the public vulnerable to fake news and misinformation. This study aims to examine the educational efforts of the Surakarta State Treasury Service Office (KPPN) through Instagram in promoting financial literacy. The findings may offer valuable insights for other institutions seeking to educate the public. An effective educational approach can improve public literacy and understanding of state finances. Using descriptive qualitative methods and content analysis, this study examined KPPN Surakarta’s Instagram posts during the third quarter of 2024. The content was categorized based on themes related to state financial education and analyzed in terms of visualization, captions, and hashtags. The results indicate that KPPN Surakarta has provided education on state finances via Instagram by incorporating credible sources, engaging visuals, informative captions, and relevant hashtags. In conclusion, the combination of source credibility, visualization, captions, and hashtags employed by KPPN Surakarta is effective in delivering financial education to the public. However, there is still room for improvement in fostering interaction with the audience.